MoveONParkinson: a mixed methods study for the development of an innovative motivational solution for personalized exercise to support PD management - Rebola, Ana Beatriz Alves (My University, 2023)
Introduction: Despite the effectiveness of physiotherapy and exercise to improve symptoms and delay disease progression, many people with Parkinson’s Disease (PwPD) do not exercise regularly. The development of the ONParkinson platform was grounded on the evidence supporting self-management technologies on PD, following the results of a survey to PwPD, their caregivers and health professionals in triad. MoveONParkinson project is focused on the platform’s exercise module, aiming to develop an innovative motivational solution for personalised exercise to promote sustained exercise adherence and PD’s more effective management. Methods: The main stages of MoveONParkinson were based on the IDEAS framework, and the features of the platform were grounded by the Social Cognitive Theory, addressing behavioural, personal and socioenvironmental influences, along with exercise self-efficacy and self-management skills to instil behaviour change. A mixed methods convergent design, using quantitative (questionnaires and System Usability Scale) and qualitative (semi-structured and thinking aloud interviews) methods were used to evaluate the Web Platform’s usability and gather feedback and assess the acceptability of the Mobile and Web interfaces, which features were drawn on recommendations for improving the exercise module of the initial prototype. Results: 28 individuals were included: 20 physiotherapists (mean age=34.50±10.4) and 8 PwPD (mean age=65.75±8.63; mean H&Y=2.0±0.76). Physiotherapists awarded the Web Platform a “Good” usability score (mean SUS=79.50±12.40; 95%CI=73.70 to 85.30) and recommended modifying features to be less time consuming and adding hybrid exercise programs. The Web and Mobile interfaces were considered valuable resources to support PD management, by promoting sustained exercise adherence through personalized exercise prescription while addressing motivation and enhancing exercise self-efficacy. Conclusions: The Web Platform’s usability scores and user’s feedback suggesting high acceptability of the digital solution make ground for evaluating its efficacy on enhancing exercise adherence trough a pilot study and subsequently its effectiveness on managing PD symptoms and improving PwPD’s quality of life.

Introdução: Apesar da efetividade da fisioterapia e do exercício físico na melhoria dos sintomas e no retardar da progressão da Doença de Parkinson (DP), muitos utentes não o praticam regularmente. A plataforma ONParkinson foi desenvolvida com base na evidência que sustenta o desenvolvimento de tecnologias para a autogestão da DP, após um inquérito direcionado à tríade (utentes, cuidadores, profissionais de saúde). O projeto MoveONParkinson pretende desenvolver a componente da plataforma direcionada ao exercício como uma solução motivacional inovadora para a sua prática, promovendo uma gestão mais efetiva da DP. Métodos: O desenvolvimento do projeto MoveONParkinson é baseado na framework IDEAS, e as funcionalidades da plataforma derivam dos construtos da Teoria da Cognição Social, aliados à autoeficácia para o exercício e estratégias de autogestão para promover a mudança comportamental. A avaliação da usabilidade da Plataforma Web, e da aceitabilidade e recolha de feedback das interfaces Web e Mobile foram efetuadas através de um estudo misto convergente, com recolha de dados quantitativa (questionários e Escala de Usabilidade do Sistema) e qualitativa (entrevistas semiestruturadas e thinking aloud). Resultados: Foram incluídos 28 participantes; 20 fisioterapeutas (média idades=34.50±10.4) e 8 utentes com DP (média idades=65.75±8.63; H&Y=2.0±0.76). Os fisioterapeutas atribuíram um bom score de usabilidade à Plataforma Web (média SUS=79.50±12.40; 95%IC=73.70; 85.30), recomendaram modificações para maior eficiência e poder criar programas híbridos. Ambas as interfaces foram consideradas ferramentas valiosas na gestão da DP, promovendo a adesão ao exercício pela prescrição personalizada aliada à componente motivacional pelo reforço da autoeficácia para o exercício. Conclusão: A boa usabilidade da interface Web, aliado ao feedback dos utilizadores e elevada aceitabilidade da plataforma ONParkinson viabilizam o planeamento de um estudo piloto para avaliar a sua eficácia em aumentar a adesão ao exercício, e posteriormente a sua efetividade na gestão da sintomatologia da DP e melhoria da qualidade de vida
Keywords: Parkinson’s Disease; Mobile Health; Exercise Self-efficacy; Exercise Adherence; Self-management; Doença de Parkinson; Mobile Health; Autoeficácia para o Exercício; Adesão ao Exercício; Autogestão